A dramaturgia de Anamaria Nunes: A era do rádio e O tambor e o anjo - Rocha, Fabrizzi Matos (2020)
This work analyzes two plays by Anamaria Nunes playwright (1950-2016): A era do Rádio - Saudades do Brasil and O Tambor e o Anjo. Based on the theoretical analysis of the drama according to Jean-Pierre Ryngaert, Lionel Abel's dramatic vision of metatheatre, the concept of intertextuality according to Kristeva and Samoyault, and the postmodern perspective conceptualized by Linda Hutcheon, and their respective studies on parody and irony. The central problem to be investigated in this work is the representation of two moments in the recent history of Brazil, through two plays. While the first dialogue with the radio, vehicle of greater reach in the period to which it refers, bringing the scene metalanguage, the second brings a problematic daily, common to many families. Both reproduce, in their own way, the Brazilian cultural and socio-political scene in the 1950s and 1970s. Intertextuality, structuring element of Anamaria Nunes' dramatic narrative, allows us to relate their dramaturgical texts to postmodern aesthetics, thanks to the irony, parody and satire employed with critical distance.